Pendidikan Agama Islam Di Sekolah Inklusi: Strategi Pembelajaran Bagi Anak Penyandang Tunalaras - Lathifah Irsyadiyah Husna; Ismail Burhanuddin; Lalu Wire Sanni Atmaja; Diyah Ayu Putri (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
Every child has the same right to get a quality education. It also emphasizes that every child with special needs, such as children with special needs, mentally unstable, has physical and psychological deficiencies, is also entitled to a proper education. In this regard, the implementation of education for children with special needs must also be considered. Children with emotional limitations are called Tunalaras. Research related to the learning of mentally retarded children has previously been carried out and has been carried out and it can be seen that the ability of self-control of mentally retarded children can be increased through better behavior improvement. So that this research is intended to find information about the process of receiving education for children with disabilities, especially Islamic religious education. This study wants to know how the process and method of learning Islamic Religious Education in inclusive schools and how Islamic Religious Education learning is carried out to be able to help change behavior for children with mental retardation. The research method used is qualitative with interviews to get as much information as possible in the field.